Comparison of breathing pattern and diaphragmatic motion in patients with unilateral cervical radiculopathy and asymptomatic group - Raziyeh Yousefiyan; Amin Kordi Yoosefinejad; Reza Jalli; Iman Rezaei (BMC Pulmonary Medicine, 2023)
Abstract Background The associations between neck pain and respiratory dysfunction were clarified in patients with neck pain. There is dearth of evidence on pulmonary dysfunction and diaphragmatic excursion in patients with unilateral cervical radiculopathy (CR). The purpose of this study was to compare the breathing pattern and diaphragmatic excursion in patients with unilateral CR with those in an asymptomatic group. Methods Twenty-five patients with unilateral CR and 25 asymptomatic individuals aged between 30 and 55 participated in this study. Diaphragmatic motion, breathing pattern, active cervical range of motion and kinesiophobia were investigated in both groups by using fluoroscopy, manual assessment of respiratory motion (MARM), cervical range of motion device, and Tampa scale of kinesiophobia. Statistical significance was set at 0.05. Results No statistically significant differences were found between the two groups with regard to sex, age and body mass index. The mean excursion of the hemi diaphragm on the involved side (the side of CR) was significantly lower than that on the uninvolved side in patients with unilateral CR with a large effect size. The excursion of the involved hemi diaphragm in patients was reduced compared to the matched hemi diaphragm in the control group. There was no significant difference between the hemi diaphragms excursion in the control group. The results of the MARM variables showed that the volume of breathing and the percentage rib cage motion in normal and deep breathing were significantly different between the two groups, but there was no significant difference in the balance of breathing between the two groups. Additionally, the active cervical range of motion was reduced in these patients in comparison to the control group, and it was less on the involved side than on the uninvolved side. Conclusion The results of this study revealed a dysfunctional breathing pattern in normal and deep breathing and a unilateral reduction in diaphragmatic excursion on the side of radiculopathy in patients with unilateral CR compared to the control group.